POPULATION DYNAMICS OF SUCKING PESTS AND THEIR CORRELATION WITH WEATHER PARAMETERS IN CHILLI, CAPSICUM ANNUM L. CROP - R. S. MEENA; O. P. AMETA; B. L. MEENA (The Bioscan, 2012)
Results revealed that the incidence of thrips (Scirthothrips dorsalis Hood), whiteflies (Bemisia tabaci Genn), aphids (Aphis gossypii Glover) and mites (Polyphagotarsonemus latus Banks) were appeared on the chilli crop soon after transplanting, while the aphid appeared little late during both the years. The peak population of thrips (14.5 and 14.7/ 3 leaves/ plant) was recorded in the first week of October, while the whitefly and aphid attained their peak in first and second week of September during 2006-07 (6.9 whiteflies/ 3leaves /plant and 9.0 aphids/ 3leaves/ plant) and during 2007-08 (6.7 whiteflies/ 3 leaves/ plant and 9.3 aphid/ 3 leaves/ plant), respectively. The mite population reached to its peak in the second week of September (9.2 and 9.0 mites/ 3 leaves/ plant) during both the years. Correlation coefficient values worked out for sucking pests incidence and weather parameters revealed that maximum temperature had positive correlation with thrips population, while negative with mite population. In case of aphid and whitefly, all the abiotic parameters were non-significant at 5 per cent level.